Xpert HPV as a Screening Tool for Anal Histologic High-Grade Squamous Intraepithelial Lesions in Women Living With HIV. (1st July 2021) - Ellsworth, Grant B.; Stier, Elizabeth A.; Chiao, Elizabeth Y.; Lensing, Shelly Y.; Darragh, Teresa; Jay, Naomi; Berry-Lawhorn, J. Michael; Einstein, Mark; Barroso, Luis F.; Cranston, Ross D.; Levine, Rebecca; Guiot, Humberto M.; et al.
Abstract : Background: Women living with HIV (WLWH) experience high rates of anal cancer. Screening using anal cytology, high-resolution anoscopy (HRA) with biopsies, can histologically diagnose anal cancer precursors called high-grade squamous intraepithelial lesions (HSIL). The low specificity of screening using anal cytology results in HRA referral for many WLWH without HSIL. Screening using high-risk human papillomavirus (HR-HPV) may improve specificity. Methods: Two hundred seven WLWH (63% non-Hispanic black) were screened for anal histologic HSIL (hHSIL) using cytology, HRA-guided biopsies, and Xpert HPV. Xpert performance for predicting anal hHSIL was compared with that of cytology. Usng Xpert 5 HPV genotypic results and accompanying cycle thresholds, receiver operator characteristic curve and recursive partitioning analyses were used to create predictive models for hHSIL. Results: The performance of Xpert to predict hHSIL was not different from that of cytology with a sensitivity (Sn) of 89% and specificity (Sp) of 49%. Interpretation of Xpert was modified using genotypic results and receiver operator characteristic curve analysis, which produced a screen with an Sn and Sp of 75% and 84% for hHSIL, respectively. Another reinterpretation of Xpert was created using recursive partitioning and cycle thresholds, which predicted hHSIL with an Sn and Sp of 75% and 86%, respectively. The detection of HPV-16 was highly predictive of hHSIL in all analyses. These modified screening tests would reduce HRA referral in this population by almost half compared with anal cytology. Conclusions: Xpert HPV is an alternative to anal cytology to screen for anal HSIL and can be optimized to reduce the number of unnecessary HRAs performed in WLWH. Abstract : Supplemental Digital Content is Available in the Text.